EFEKTIVITAS KONSELING KELOMPOK BEHAVIORAL DENGAN TEKNIK SELF MONITORING UNTUK MENINGKATKAN SELF REGULATED LEARNING SISWA KELAS X-E14 DI MAN 1 SURAKARTA TAHUN PELAJARAN 2024/2025: Pendekatan Behavioral dengan Teknik Self Monitoring untuk Meningkatkan Self Regulated Learning pada Siswa pada Siswa Kelas X-E14 di MAN 1 Surakarta.. - hanifah, devina putri nur; Sri Suryanti, Hera Heru; Putro, Eko Adi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
EFEKTIVITAS KONSELING KELOMPOK BEHAVIORAL DENGAN TEKNIK SELF MONITORING UNTUK MENINGKATKAN SELF REGULATED LEARNING SISWA KELAS X-E14 DI MAN 1 SURAKARTA TAHUN PELAJARAN 2024/2025. This study aims to determine the effectiveness of group counseling using a behavioral approach with the self-monitoring technique in improving self-regulated learning among students of class X-E14 at MAN 1 Surakarta in the 2024/2025 academic year. The behavioral approach is a scientific perspective on human behavior. Self-monitoring is a form of self-awareness used by counselees to evaluate the tendencies of their habits, thoughts, or feelings. This study employed a quantitative experimental method. The population consisted of all students of class X-E14 at MAN 1 Surakarta in the 2024/2025 academic year. The sample comprised 6 students who had low levels of self-regulated learning. Data analysis was conducted using the Paired Sample T-test. Based on the analysis results regarding the effectiveness of behavioral group counseling using the self-monitoring technique to improve self-regulated learning among class X-E14 students at MAN 1 Surakarta, a significance value (2-tailed) of 0.000 < 0.05 was obtained. Therefore, it can be concluded that behavioral group counseling using the self-monitoring technique is effective in improving self-regulated learning among class X-E14 students at MAN 1 Surakarta in the 2024/2025 academic year.